C-reactive protein point-of-care testing and antibiotic prescribing for acute respiratory tract infections in rural primary health centres of North Ethiopia: a cross-sectional study - Yebyo, Henock (NPJ Prim Care Respir Med, 2016)
Unjustified antibiotic prescribing for acute upper respiratory infections (URTIs) is probably more common in poor-resource settings where physicians are scarce. Introducing C-reactive protein (CRP) point-of-care testing in such settings could reduce the misuse of antibiotics, which could avert antibiotic resistance. However, information useful for the applicability of CRP test in resource-limited settings is lacking. This study aimed to elicit the frequency of antibiotic prescribing and distribution of CRP levels in remote, rural settings in Ethiopia. We included 414 patients with acute URTIs from four health centres. Health professionals recorded the clinical features of the patients, but the laboratory professionals measured the CRP levels of all patients at the point of care. The most prominent respiratory causes for consultation were acute URTIs combined (44.4%), and lower respiratory tract infections—pneumonia (29.71%) and acute bronchitis (25.84%). The CRP distribution was <20 mg/l, 20–99 mg/l and 100 mg/l or more in 66.6%, 27.9% and 5.5% of the patients, respectively. The CRP levels were significantly different among these clinical diagnoses (X(2)=114.3, P<0.001, d.f.=4). A wide range of antibiotics was administered for 87.8% of the patients, regardless of the diagnostic or prognostic nature of their diseases. Antibiotic prescribing for acute URTIs in the rural areas of Ethiopia is unduly high, with high proportions of mild, self-limiting illness, mostly URTIs. Implementation of CRP point-of-care testing in such resource-constrained settings, with low- or middle-grade healthcare professionals, could help reconcile the inappropriate use of antibiotics by withholding from patients who do not benefit from antibiotic treatment.